Predictors and Management of Hepatic Encephalopathy after Transjugular Intrahepatic Portosystemic Shunt: The Current State of Literature - Ju, Connie; Fortune, Brett E.; Karuppasamy, Karunakaravel; Kapoor, Baljendra (Digestive Disease Interventions, 2018)
Hepatic encephalopathy is a well-known sequela of transjugular intrahepatic portosystemic shunt (TIPS) insertion, but objective clinical and laboratory predictors remain poorly elucidated. Numerous medical and interventional strategies have also been described, though little consensus has been reached on the optimal treatment technique to improve morbidity and mortality in patients who develop refractory encephalopathy. To improve TIPS candidate selection and prognostication, this review consolidates predictive factors for post-TIPS encephalopathy and offers an updated description of historical and contemporary interventional techniques for management. Despite the abundant literature on treatment strategies, large studies directly comparing outcomes between the various techniques are nonexistent.
Keywords: hepatic encephalopathy; TIPS; predictors; management